A convergent preparation of the CHK1 inhibitor MK-8776 (SCH 900776). Issue 24 (15th June 2016) - Labroli, Marc A.; Dwyer, Michael P.; Poker, Cory; Keertikar, Kerry M.; Rossman, Randall; Guzi, Timothy J.
Graphical abstract: Highlights: A highly convergent preparation of the CHK1 inhibitor MK-8776 is described. Efficient cyclocondensation reaction to form the pyrazolo[1, 5- a ]pyrimidine core. Key insights made into the retention of optical purity during the cyclocondensation reaction. Abstract: This Letter describes the development of a convergent, efficient route to the CHK1 inhibitor MK-8776. This synthetic approach relies upon the cyclization of a bispyrazole adduct10 with a optically pure β-keto nitrile9 to construct the pyrazolo[1, 5- a ]pyrimidine scaffold in a single step.